Analogía de las corrientes de relaciones públicas en las Américas (2002)
The author’s aim is a comparative study of the social vision in Public Relations among the various dominant schools In the United States, and the different views applied in Latin America. The author defines social roles from these perspectives -pragmatic, conservative, radical and idealistic and discuss a new critical perspective for theory and practice In Public Relations which he calls postmodern. Based on recent studies, the author claims that ordinary citizens keep more and more watch on moral organizational behavior, which challenges professionals to guarantee the organizations communicate in an ethical and responsible manner. Finally, the author affirm that the various professional viewpoints to point out the Public Relations Professional’s function as active and transforming, an aspect in which some American researches coincide with their Latin American colleagues. He illustrates the case of Brazil to point out possible lines of action for this part of the Continent